1) -2m üssü4.3m üssü2.4m=

2) 5x üssü2 y.4xy üssü3=

3) 2xüssü3.2xüssü3.2x=

4) 2xüssü3+2xüssü3+2xüssü3=

5) 3.(2x-5)=

6) 2x.(4-3x)=

7)3xüssü2.(2xüssü-5x+4)=

8)5.(3x+5y)-4.(2y-6x)=

9)4a.(2a-5)-2s(8+3a)=

10) 2a(3a-5b)-4b.(4a+3b)=

11)2.(3x+5)+4.(9-2x)=

12)4x.(2x+3x üssü2)-2x üssü2.(3x+5)=

13) (2x+3).(3x+5)=

14) (x-2).(x+3)=

15) (a+b).(a-b)=

16) (2x-3).(.x+4)=

17) (x+y) üssü2=

18) (x üssü2+5).(3x+2xüssü2)=

1

Cevaplar

2016-10-18T09:25:08+03:00
5 -5
6- 8
7- 28
8 - 6
9-9
10-7

tam emin değilim


0